Association of Subjective Sleep Quality and Glycemic Level in Patients with Type 2 Diabetes Mellitus: A cross sectional study - Khakurel, G.; Shakya, D.; Chalise, P.; Chalise, S. (Kathmandu University Medical Journal, 2020)
Background Sleep disorders are considered as one of the important risk factor which have a great impact on patients with type 2 diabetes mellitus. Objective The objectives of this study was to determine the effect of sleep quality on the glycemic level among type 2 diabetic patients. Method This was a cross sectional study done in 208 type 2 diabetic patients visiting Kathmandu Medical College Public Limited from July 2019 to December 2019. Data regarding sleep quality was collected by using Pittsburgh Sleep Quality Index taking global cut off score ≥ 8 as poor sleeper. Glycated hemoglobin level ≥ 7 was considered as poor glycemic control. Chi square test was used to compare parameters between good sleeper and poor sleeper. Independent sample t test compared the means of Pittsburgh Sleep Quality Index factors and glycemic contol. A logistic regression analysis of Pittsburgh Sleep Quality Index factors and glycated hemoglobin was done. Values of p ≤ 0.05 were considered statistically significant. Result The study findings revealed that 62 % had poor glycemic control and 58.7 % were poor quality sleeper. There was a significant association of sleep quality with glycemic control and duration of diabetes. Logistic regression analyses showed that subjective sleep quality was risk factor for poor glycemic control. The odds ratio for subjective sleep quality was found to be 4.59 (2.13-9.91). Conclusion Poor sleep quality was common in type 2 diabetic patients. This study showed that the risk factors for poor subjective sleep quality include poor glycemic control and longer duration of diabetes mellitus.